INFLUENCE OF REPETITIVE WORK ON WORK PRODUCTIVITY ON DEPARTMENT OF PACKAGING: INFLUENCE OF REPETITIVE WORK ON WORK PRODUCTIVITY ON DEPARTMENT OF PACKAGING - Walujo, Djoko Adi (UNIPA PRESS, 2018)
Sealing process requires an ergonomic attitude in work. If work posture is not ergonomic it can cause musculoskeletal system disorders. The purpose of this research to know the effect of repetitive work on work productivity on sealing activities in the packaging department based on RULA method. Data collection is done by direct observation and interview. Data obtained are analyzed, then the acquisition of grand scores is categorized based on the action level of the RULA. The posture of sealing process in the packaging department is in the fourth level action category which means that there is need for investigation and possible repairs.